Quantitative analysis of the relationship between maxillary incisors and the incisive canal by cone-beam computed tomography in an adult Japanese population - Tomonari Matsumura; Yuji Ishida; Ayako Kawabe; Takashi Ono (SpringerOpen, 2017)
Abstract Background In setting goals for orthodontic treatment, determining the morphologies of the alveolar bone and maxillary incisor root is important for avoiding root resorption, dehiscence, and fenestration. This study aimed to analyze the configurational relationships among maxillary incisors, the alveolar border, and the incisive canal by cone-beam computed tomography (CBCT). Methods Cone-beam CT images of 93 orthodontic patients were evaluated for length of the incisive canal (L); angles between the palatal plane and the maxillary alveolar border (θ1), the incisive canal (θ2), and maxillary incisor (θ3); distance from the left maxillary incisor to the incisive canal (D); and cross-sectional areas of the incisive canal (CSAs) at three vertical levels. Comparison of variables between male and female patients was performed with the two-sample t test. Correlations between parameters were examined by Pearson's correlation analysis and Bonferroni correction for multiple comparisons. Results Male patients exhibited significantly greater values of L than female patients. There were significant positive correlations between θ1 and θ2, θ2 and θ3, and θ3 and θ1. While the value of D was the lowest at the oral opening, that of the cross-sectional area of the incisive canal (CSA) was the greatest at the incisal root apex. Conclusions This study demonstrated that the incisive canal had large inter-individual variability, and the proximity between the incisive canal and the incisal root could not be precisely predicted by the conventional cephalograms. Therefore, pre-treatment CBCT examination should be recommended when a large amount of maxillary anterior retraction and/or intrusion is planned in orthodontic diagnosis.